Jaime Escobar - Technical and Operational Feasibility, for the business analysis, of running an AutopistaFerroviariawith Iberian track gauge between Port of Algeciras and Zaragoza-Plaza - Escobar, Jaime (Jornada de Jóvenes Investigadores del I3A, 2020)
Póster presentado en la IX Jornada de Jóvenes Investigadores del I3A